Palæstra i O-D-I-N’s træningsanlæg - Worm, Ole (Forum for Idræt, 2003)
Danske OL-deltageres møde med de olympiske lege. Bl.a. svømmeren Jytte Hansen i 1948. PALÆSTRA in O-D-I-N’s training facility The shrines at Olympia, Delphi, Isthmia and Nemea took their turn in fixed rotation to organize festivals in which sporting competitions were a central element. They were characterised by being ”stefanoforos”, which is to say that the victor would be wreathed and not directly rewarded with gifts. Preparatory training in situ was a requirement. This took place at a training facility separate from the shrine and from the competition ground. Palæstra was part of this facility. Facilities of this kind of differing sizes have been dated and identified at Olympia and Delphi, and excavations are in progress to find similar sites at the other two shrines in the north-western Peloponnese. American archaeologists on location have found traces which are reported to be promising. This arena for wrestling and fighting with its square building was the site of both physical and intellectual training and from the beginning developed in Hellenic architectural activity in ways that correspond to other secular buildings. Where palæstra in the city state was part of the everyday life of men and boys, this training facility in OD- I-N became the site of an unadulterated presentation of an example of the good life.